The Effect of Reduction Parameters on Iron Nugget Production From Composite Pellets - Birol, Burak; Saridede, Muhlis Nezihi (TAYLOR & FRANCIS INC, 2013)
Composite pellets which contain a reducing agent and are produced only by cold bonding process are improved instead of traditionally hardened pellets by sintering. The new ironmaking technologies that are able to utilize these pellets have been developed from pilot plant to commercial scale. Iron nuggets which have a similar composition to pig iron can be produced by using composite pellets at high temperatures (13501400 degrees C) and in a short reduction time (1520 min) by smelting reduction process. In this study, the effect of reduction parameters and basicity of composite pellets on the reduction properties and product quality are investigated. Composite pellets containing magnetite concentrate with a reducing agent (coke) and a flux are processed at different temperature and at times by smelting reduction process. The increasing temperature and time has a positive effect on reduction and melting of the pellets. Excessive carbon prevents the metal droplets from coalescing. The iron nugget that is produced from the sample with the basicity (CaO/SiO2) of 0.68 has the optimal physical and chemical properties. It is also determined that a decrease or increase of basicity has a negative effect on the properties of the iron nuggets.
Keywords: basicity; composite pellet; iron nugget; reduction; smelting reduction; PIG-IRON; COAL; IRONMAKING; Metallurgy & Metallurgical Engineering; Mining & Mineral Processing